2009
DOI: 10.1017/s0266467409990344
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of seed rain and seedling regeneration in abandoned agricultural clearings in a seasonally dry tropical forest in India

Abstract: Abstract:Forest recovery in abandoned pastures and agricultural fields is often impeded, therefore it is important to understand the factors limiting regeneration. Patterns of seed arrival and regeneration in five abandoned agricultural clearings nested within a seasonally dry tropical forest in India were examined along five transects radiating from the forest edge into the clearings. Wind-dispersed seeds dominated the seed arrival in clearings compared with vertebrate-dispersed seeds: 5563 wind-dispersed see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…) and anthropogenic‐disturbed forests (Teegalapalli et al . ), as reported in our study. Nonetheless, despite the predominance of autochorous species in our study, species dispersed by animals were least represented in the young forest, indicating that dispersal by animals has not yet been completely re‐established.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…) and anthropogenic‐disturbed forests (Teegalapalli et al . ), as reported in our study. Nonetheless, despite the predominance of autochorous species in our study, species dispersed by animals were least represented in the young forest, indicating that dispersal by animals has not yet been completely re‐established.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the predominant dispersal syndrome in dry environments tends to vary with aridity and the predominance of life forms (herbs, vines, shrubs or trees). In some dry forests, dispersal by animals predominates (Griz & Machado 2001;Jara-Guerreiro et al 2011;Mart ınez-Garza et al 2011)' however, in other forests (primarily in semiarid environments), self-dispersal and wind dispersal predominate in both mature (Machado et al 1997;Ara ujo et al 2007;Lima et al 2008) and anthropogenic-disturbed forests (Teegalapalli et al 2010), as reported in our study. Nonetheless, despite the predominance of autochorous species in our study, species dispersed by animals were least represented in the young forest, indicating that dispersal by animals has not yet been completely re-established.…”
Section: Factors Limiting Seed Rain and Implications For Recolonisatisupporting
confidence: 70%
“…Previous studies show that forest amount and proximity are positively correlated with bird abundance and composition (Lindenmayer et al 2010, Van Bael et al 2013, and many authors suppose that seed rain and seedling recruitment should respond similarly , Rodrigues et al 2009, Tambosi et al 2013). However, empirical evidence has been mixed with some studies finding landscape effects on forest regeneration (Purata 1986, Teegalapalli et al 2010) and others not (Howe et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Several studies in regions with healthy frugivore communities have directly monitored seed rain and seedling recruitment in degraded areas adjacent to intact forests and have shown that vertebrate frugivores do move seeds, sometimes from far away, into degraded areas, often acting as the major (or only) source of native seed rain (e.g. [18], [19], [32][35]). The importance of vertebrate seed dispersal has been recognized by the implementation of restoration techniques which encourage dispersal, such as the planting of fruiting trees and ‘tree islands’ within degraded areas [36][38].…”
Section: Introductionmentioning
confidence: 99%